2021
DOI: 10.1101/2021.07.07.21260132
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aorta-on-a-chip reveals impaired mitochondrial dynamics as a therapeutic target for aortic aneurysm in bicuspid aortic valve disease

Abstract: BackgroundBicuspid aortic valve (BAV) is the most common congenital cardiovascular disease in general population and is frequently associated with the development of thoracic aortic aneurysm (TAA). There is no effective strategy to intervene with TAA progression due to an incomplete understanding of the pathogenesis. Insufficiency of NOTCH1 expression is highly related to BAV-TAA, but the underlying mechanism remains to be clarified.MethodsA comparative proteomics analysis was used to explore the biological di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In contrast to traditional cell culture techniques, which often fail to mimic the physiological environment of cultured cells, recent studies have shown that microfluidic chip technology can mirror natural cellular development processes to yield more accurate physiological characteristics. 23 Although animal models are widely used to study AA, species differences, high costs, and time limitations hinder their applicability in pharmaceutical drug screening. Our hiPSC-SMC-based organ-on-a-chip may be a suitable complement to animal models for mechanistic research and drug screening for AA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to traditional cell culture techniques, which often fail to mimic the physiological environment of cultured cells, recent studies have shown that microfluidic chip technology can mirror natural cellular development processes to yield more accurate physiological characteristics. 23 Although animal models are widely used to study AA, species differences, high costs, and time limitations hinder their applicability in pharmaceutical drug screening. Our hiPSC-SMC-based organ-on-a-chip may be a suitable complement to animal models for mechanistic research and drug screening for AA.…”
Section: Discussionmentioning
confidence: 99%
“…We have described micro-physiological model fabrication and mechanical stimulation parameters in detail in our previous study. 23 To replicate different strains on the human aortic wall, we applied 7.15 ± 0.45% strain induced by a vacuum pressure of 10 kPa as a relatively low strain and 17.25 ± 0.95% strain induced by a vacuum pressure of 15 kPa as a relatively high strain. The liquid channel part of the LM-SMC, NC-SMC, or PM-SMC chips was connected in series as an entire lineagespecific SMC-on-a-chip, driven by a liquid pump, and the culture medium maintained uninterrupted circulation.…”
Section: Design and Construction Of Micro-physiological Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of leflunomide to improve mitochondrial dynamics has been used to treat pancreatic cancer and mitral aortic valve disease. Enhanced mitochondrial fission inhibits metastasis in triple-negative breast cancer, and leflunomide has been shown to counteract this inhibitory effect (81)(82)(83).…”
Section: Leflunomidementioning
confidence: 99%